A hybrid metaheuristics approach for a multi-depot vehicle routing problem with simultaneous deliveries and pickups. (5th August 2019) - Rajak, Sonu; Parthiban, P.; Dhanalakshmi, R.
Multi-depot vehicle routing problem with simultaneous deliveries and pickups (MDVRPSDP) is a variant of classical vehicle routing problem (VRP), which has often encountered in real-life scenarios of transportation logistics; Where, vehicles are required to simultaneously deliver the goods and also pick-up some goods from the customers. The current scenario importance of reverse logistics activities has increased. Therefore it is necessary to determine efficient and effective vehicle routes for simultaneous delivery and pick-up activities. MDVRPSDP, which is very well-known non-deterministic polynomial-hard (NP-hard) and combinatorial optimisation (CO) problem, which requires metaheuristics to solve this type of problems. In this context, this article presents a hybrid metaheuristic which combines simulated annealing (SA), ant colony optimisation (ACO) and along with long-arc-broken removal heuristic approach for solving the MDVRPSDP. The preliminary results show that the proposed algorithm can provide good solutions.